Variables demográficas clínicas y calidad de vida de pacientes con antecedentes de COVID–19 atendidos en la unidad de cuidados intensivos Hospital Regional de Loreto Iquitos 2024 - Rodríguez López, Lizbeth Marisel (2025)
The objective was to determine the relationship between clinical demographic variables and quality of life in patients with a history of COVID - 19, treated in the Intensive Care Unit of the Regional Hospital of Loreto Iquitos 2024. The method was quantitative, non-experimental descriptive, correlational and cross-sectional design. The population and sample consisted of 83 patients with a history of COVID - 19, who were treated in the Intensive Care Unit of the Regional Hospital of Loreto. The technique was the survey and the home visit. The instruments were the Demographic and Clinical Data Sheet of Patients with a History of COVID - 19 and the SF 36 Quality of Life Questionnaire. For data processing, the SPSS version 24.0 statistical package was used and, to establish the relationship of the study variables, the non parametric distribution-free inferential statistic called Chi Square (X2) was used with a significance level of α 0.05. The results on the demographic and clinical variables of the patients, 33.7% (28) were 46 to 55 years old, 61.4% (51) were male, 38.6% (32) were in the ICU for 7 to 15 days, 86.7% (72) received mechanical ventilation and 38.6% (32) suffered from hypertension. Regarding the level of quality of life, 78.3% (65) demonstrated having a better quality of life. In conclusion, a significant statistical relationship was found between demographic variables: age (p=0.000), sex (p=0.001), and clinical variables: length of stay in the Intensive Care Unit (p=0.004), mechanical ventilation (p=0.000), and comorbidity (p=0.024) and quality of life in patients with a history of COVID-19.